Invariância de rótulo, termos de superfície e simetria de calibre em diagramas de Feynman a um laço em eletrodinâmica quântica - Jose Roberto Pereira Junior (2011)
The purpose of the present work is to shed light on the relationship between momentum routing invariance surface terms and gauge invariance using quantum electrodynamics as a working example. We discuss two approaches. On one hand, Mc Keon and collaborators, within a 4-dimensional approach, agree that choosing a particular routing in the internal momentum implements gauge invariance. On the other hand, in the approach we discuss here we establish momentum routing invariance as a fundamental symmetry of a Feynman diagrams. We verify that setting surface terms which are by products of workings in Implicit regularization automatically delivers gauge and momentum routing invariance amplitude in quantum electrodynamics at one loop order